A method for correcting breathing‐induced field fluctuations in T2*‐weighted spinal cord imaging using a respiratory trace. Issue 6 (8th February 2019) - Vannesjo, S. Johanna; Clare, Stuart; Kasper, Lars; Tracey, Irene; Miller, Karla L.
Abstract : Purpose: Spinal cord MRI at ultrahigh field is hampered by time‐varying magnetic fields associated with the breathing cycle, giving rise to ghosting artifacts in multi‐shot acquisitions. Here, we suggest a correction approach based on linking the signal from a respiratory bellows to field changes inside the spinal cord. The information is used to correct the data at the image reconstruction level. Methods: The correction was demonstrated in the context of multi‐shot T2*‐weighted imaging of the cervical spinal cord at 7T. A respiratory trace was acquired during a high‐resolution multi‐echo gradient‐echo sequence, used for structural imaging and quantitative T2* mapping, and a multi‐shot EPI time series, as would be suitable for fMRI. The coupling between the trace and the breathing‐induced fields was determined by a short calibration scan in each individual. Images were reconstructed with and without trace‐based correction. Results: In the multi‐echo acquisition, breathing‐induced fields caused severe ghosting in images with long TE, which led to a systematic underestimation of T2* in the spinal cord. The trace‐based correction reduced the ghosting and increased the estimated T2* values. Breathing‐related ghosting was also observed in the multi‐shot EPI images. The correction largely removed the ghosting, thereby improving the temporal signal‐to‐noise ratio of the time series. Conclusions: Trace‐based retrospective correction of breathing‐induced field variations can reduce ghosting and improve quantitative metrics in multi‐shot structural and functional T2*‐weighted imaging of the spinal cord. The method is straightforward to implement and does not rely on sequence modifications or additional hardware beyond a respiratory bellows.